Soluble B7-H5 Is a Novel Diagnostic, Severity, and Prognosis Marker in Acute Pancreatitis. (8th October 2021) - Xu, Ruoxin; Gong, Ju; Chen, Wei; Jin, Yakang; Huang, Jian
Abstract : As an important ligand in T lymphocyte costimulatory pathways, B7-H5 is involved deeply in the immune response in various diseases. However, its clinical usefulness as an early indicator in acute pancreatitis (AP) remains unclear. In this study, the levels of sB7-H5 and cytokines in plasma samples of 75 AP patients, 20 abdominal pain patients without AP, and 20 healthy volunteers were determined. Then, the correlation of sB7-H5 and clinical features, cytokines, the Ranson score, APACHE II score, Marshall score, and BISAP score was analysed, and the value of sB7-H5 for diagnostic, severity, and prognosis of AP was evaluated. We found that the levels of sB7-H5 were specifically upregulated in AP patients. Receiver operating characteristic (ROC) analysis revealed that sB7-H5 can identify AP patients from healthy or abdominal pain patients with 78.9% or 86.4% sensitivity and 93.3% or 90.0% specificity. Further analysis showed that the levels of sB7-H5 were significantly correlated with WBC (p = 0.004 ), GLU (p = 0.008 ), LDH (p < 0.001 ), Ca 2+ (p = 0.006 ), AST (p = 0.009 ), PLT (p = 0.041 ), IL-6 (p < 0.001 ), IL-10 (p < 0.001 ), and TNF- α (p < 0.001 ). And levels of sB7-H5 were gradually increased among patients with mildly acute pancreatitis (MAP), moderately severe acute pancreatitis (MSAP), and severe acute pancreatitis (SAP). It can distinguish the severity of AP with good sensitivity and specificity. Moreover, when dividing the patients into two groups according to the median level of sB7-H5, the local complication and length of stay of low levels of the sB7-H5 group were significantly less than those in high levels of the sB7-H5 group. And the levels of sB7-H5 in AP patients were significantly correlated with the Ranson score (p < 0.001 ), APACHE II score (p < 0.001 ), Marshall score (p < 0.001 ), and BISAP score (p < 0.001 ). The AUCs of assessing local complications of sB7-H5 at day 1 and day 3 were 0.704 (p = 0.0024 ) and 0.727 (p = 0.0373 ). These results showed the potential value of sB7-H5 as a diagnostic, severity, and prognosis marker of AP.